Utilisation Du Sig Dans L’analyse Morphometrique Et La Prioritisation Des Sous-Bassins Versants De Oued Inaouene (Nord-Est Du Maroc) - Brahim, Benzougagh; Larbi, Boudad; Abdallah, Dridri; Driss, Sdkaoui (European Scientific Journal (Kocani), 2016)
The present work focuses on the prioritization of the wadi Inaouène watershed based on morphometric analysis. The river system was extracted and thirteen sub-catchment basins have been delineated from a DTM using open source software. The following morphometric parameters were calculated for each sub-basin stream length (Lu) and the average length (Lsm), flow length ratio (RL), bifurcation ratio (Rb), medium bifurcation ratio (RBM), drainage density (Dd), drainage texture (T), the flow rate (Fs), elongation rate (Re), circularity ratio (Rc), form factor (Ff), topography and terrain ratio. By combining the values of these parameters we have classified the sub-watersheds in three prioritization categories: high grade (SBV01, SBV04, SBV05, SBV06, SBV11 and SBV12), is subject to a maximum soil erosion, which requires immediate action to prevent possible natural hazards, the Average category (SBV02, SBV03, SBV07, SBV08, SBV09 and SBV10) and low grade (SBV13).